A study on common English questions used by third-year students of English department, university of Foreign Language studies, the university of DaNang - Phan,Thị Mỹ Thương; Trần Quang Hải, Ph.D. (Đà Nẵng : The University of Da Nang, 2015)
This thesis mainly aims to know deeply how English conversations are politely maintained in terms of raising questions. The practical use of English was also taken into account. In practice, the study attempted to identify and describe 778 common English questions from 30 conversations used by 69 third-year students (academic 2012-2016) by recording and eliciting information of the given questionnaire for finding out their difficulties in maintaining conversations effectively and to look into their linguistics errors so that we can provide some pedagogical suggestions to help the Third-year students to avoid interrupting their English conversations and making mistakes in English speaking. The study also attempts the main causes that prevent the students from being able to keep their conversations effectively, suggest some suggestions for learning English speaking.
Master thesis in the English language. Field: The
Includes apendix and reference (p. 69-72).
Keywords: common English questions used by third-year students of English department; English questions used by third-year students -- English questions used; The English language